Penggunaan Alat Peraga Kerangka Tulang Kardus (KETUKAR) dalam Pembelajaran IPAS di Kelas IV Sekolah Dasar - Jannah, Nanik Syafiratul; Prayogo, Muhammad Suwignyo; Az-zahra, Aisyah; Imelliya, Febbi (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
Teaching aids in science education serve as supporting media that help clarify students' understanding of science concepts through the presentation of concrete objects. The use of teaching aids can make the learning process more interesting and efficient. The purpose of this study was to examine the use of cardboard skeleton teaching aids (KETUKAR) in science learning for fourth-grade students at Mangli 01 Public Elementary School in Jember. The method used in this study was a descriptive qualitative method that used data collection techniques through interviews, observation, and documentation using inductive data analysis techniques. The results of the study show that the use of teaching aids (KETUKAR) is effective in improving students' understanding because it helps them visualize abstract skeletal system concepts more concretely. The researcher suggests that future studies should refine teaching aids to make them more creative and dynamic.